Tenecteplase versus alteplase in patients with acute ischemic stroke: an updated systematic review and meta-analysis - Abdelmonam M. Hagag; Muhammed E. Kormod; Mahmoud Elmwafy Ads; Mennatullah A. El-Refaay; Omnia M. Abozaid; Omar A. Ghanem; Mazen Yasser; Karim M. Abdelmoaty; Alaa Mahmoud Khedr; Gregory W. Albers (European Journal of Medical Research)
Abstract Background Stroke was the second leading cause of death and the third leading cause of disability worldwide in 2019. Alteplase is an FDA-approved medication for the treatment of patients with ischemic stroke within 4.5 h. However, Tenecteplase is an alternative. We aimed to assess the safety, efficacy, and the best dose of tenecteplase vs alteplase. Methodology We followed the PRISMA 2020 guidelines. We searched PubMed, Scopus, Web of Science, and the Cochrane Library until November 2024. We included RCTs that compared tenecteplase with alteplase in acute ischemic stroke patients within 4.5 h of onset. Relative risk, 95% CI, and random effects models were used. Our primary endpoints were excellent functional outcomes and mortality. An excellent functional outcome was defined as a modified Rankin Score of 0–1 at 90 days. The Risk of Bias 2 tool from Cochrane was used to assess the quality of the studies. Results Thirteen RCTs met our inclusion criteria, including 9053 patients, 4416 of whom had tenecteplase. Six studies showed a low risk of bias, and the other 7 had some concerns either in their randomization process or in the deviation from the intended intervention. Tenecteplase 0.25 mg/kg had a significantly better performance in achieving excellent functional outcomes (p value 0.008), but no difference was observed in mortality rates (P value 0.37). On the other hand, no difference was observed in comparing either TNK 0.1 mg/kg or TNK 0.4 mg/kg versus alteplase in the reported outcomes. A meta-regression revealed that a reduction in the baseline NIHSS score had a significant effect on favorable functional outcomes (P value 0.025). Sensitivity analysis for outcomes comparing either TNK 0.25 mg/kg and TNK 0.1 mg/kg versus alteplase showed that no single study removal affected the significance of the study, while Kvistad 2022 and Logallo 2017 removal changed the significance of outcomes comparing TNK 0.4 mg/kg versus alteplase. Conclusion When compared with alteplase, 0.25 mg/kg tenecteplase is superior for achieving excellent functional outcomes and is not inferior in terms of major neurological improvement or death rates. TNKs at 0.25 mg/kg appear to be the optimal dose and a desirable alternative to alteplase. PROSPERO Registration Number CRD42024596896